G148(P) Safe and timely stepdown from an internal picu: a patient safety priority but one full of challenges. (25th October 2020) - Evans, K; Stephenson, W; Porter, A; Senanyake, U; Zoeteman, J; Hodin, M; Prince, N
Abstract : Background: Children recently discharged from Paediatric Intensive Care units (PICU) are likely to have on-going complex medical needs and are at significant risk of deterioration. Local and national standards are in place to ensure that these children are reviewed in a safe and timely manner. Aims: This Quality improvement Project (QIP) assessed the internal 'step-down' process of patients from the PICU to the paediatric wards with intention of improving communication and documentation between these two teams. Methods: Retrospective audit of PICU discharge communication, documentation and time to ward review for all patients discharged during October 2018. Novel 'PICU discharge summary' and 'Verbal Handover' templates to be used the on local patient management system (PMS) were devised following consensus between PICU and paediatric consultants. Re-audit of PICU discharge data was performed after the new templates were in routine use. Results: Discharge data was reviewed for the 35 children discharged from PICU to the ward in October 2018. 31 cases were studied in the second audit cycle (September 2019). Table 1 compares key differences after implementation of the changes. Table 2 compares timing of PICU discharges between the two audit cycles. Conclusions: Introduction of a PICU verbal handover template for the hospital PMS significantly improved verbal handover from PICU to ward teams in our trust. However mean time to ward review following PICU handover remains sub optimal. Most patients are discharged from PICU during the afternoon or out of hours, this may explain the lengthy time to ward review as these times are likely busier and with less staff. Further QIP involving multidisciplinary teams to improve PICU discharge planning would be beneficial.